Mekanisme Corporate Governance dan Penghindaran Pajak dengan Ukuran Perusahaan sebagai Variabel Pemoderasi - Yunianto, Andan; Harjanti, MG. Fitria; Purwati, Eti; Murtin, Alek (E-Jurnal Akuntansi; Vol 33 No 5 (2023)DO - 10.24843/EJA.2023.v33.i05.p05, 2023)
The purpose of this research is to provide empirical evidence about corporate governance mechanisms consisting of institutional ownership, the proportion of independent commissioners and audit quality that affect tax evasion with firm size as a moderating variable. The samples used were 152 companies from manufacturing companies listed on the Indonesia Stock Exchange. Data analysis technique using Moderated Regression Analysis (MRA). This study found evidence that institutional ownership has a negative effect on tax evasion. The results differ from the independent board of commissioners and audit quality which have no effect. In addition, it was also found evidence that company size weakens the negative effect of institutional ownership on tax avoidance, but is unable to strengthen or weaken the effect of an independent board of commissioners and audit quality on tax avoidance. Keywords: Tax Avoidance; Corporate Governance; Audit Quality; Institutional Ownership;  Firm Size